“PENGARUH PROFITABILITAS, LIKUIDITAS, TANGIBILITY, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia untuk Tahun 2013-2016)” - Aldila Nandia Cita, 14.05.52.0112; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2018)
The purpose of this researchwas to examines the effect of Profitability, Liquidity, Tangibility, and Firm Size to Capital Structure on property and real estate companies listed on the Indonesia Stock Exchange for period 2013-2016.This research was quantitative and the data type includes time series data. The sample of this research used purposive sampling method. Based on certain criteria, there were 52 companies that matched with the sample. The statistical method used in this research was multiple regression. Based on result from data analysis, Profitability has the negative effect and significant to Capital Structure with t value -2,382 and significant value 0,018. Liquidity also has negative effect and significant to Capital Structure with t value -2,086 and the significancy amount 0,039. Tangibility has negative effect and not significant to Capital Structure with t value amount -0,868 and significant value 0,387. Whereas the Firm Size has negative effect and significant to Capital Structure with t value amount -2,036 and significant value amount 0,043.Keywords: Profitability, Liquidity, Tangibility, Firm Size, and Capital Structure.